A new scheme for large marine vessels LNG cold energy utilization from thermodynamic and thermoeconomic viewpoints. (1st February 2021) - Ouyang, Tiancheng; Tan, Jiaqi; Xie, Shutao; Wu, Wencong; Su, Zixiang
Graphical abstract: Highlights: Advanced scheme for cold energy recovery of marine natural gas engine is proposed. The best working fluids for different modules are determined. Comprehensive optimization of the whole system is realized by genetic algorithm. Power and exergy efficiency of cold energy recovery are increased by 20.45% and 7.71%. Abstract: With the implementation of International Maritime Organization's new emission regulations in 2020, it has a huge impact on shipping industry. To meet the strict emission regulations and policies, liquefied natural gas, as a promising fuel, can replace the traditional heavy oil, and effectively and practically act as the main power source of marine engine. When liquefied natural gas is vaporized from −162 °C to room temperature, a large amount of cold energy is released to the outside world. To reuse the cold energy efficiently and economically, a new scheme integrated with organic Rankine cycle, seawater desalination, subzero storage and air-conditioning is proposed through comparison of six solutions. With a series of analysis and comparison, R290, NH3, R32 and R152a are determined as the best working fluids for organic Rankine cycle, subzero storage, seawater desalination and air-conditioning modules, respectively. After optimizing the parameters of the scheme by genetic algorithm, the exergy efficiency, net work and payback period reach 55.91%, 210.3 kW and 4.27 years, respectively, showing excellent thermoeconomic performance. Therefore, the proposed method provides a new idea for cold energy recovery of natural gas engine on ships.